2023
DOI: 10.1037/apl0001089
|View full text |Cite
|
Sign up to set email alerts
|

Being on the same page matters: A meta-analytic investigation of leader–member exchange (LMX) agreement.

Abstract: Although leader-member exchange (LMX) theory offers a detailed account of leader-follower relationship building, the importance of LMX agreement as a theoretically meaningful relational phenomenon has received less attention. This has, in turn, limited scholarly understanding of its pivotal role in leaderfollower relationships. We conducted a meta-analysis to synthesize the substantive implications of LMX agreement for leader-follower relationships and to further understand which factors may influence its vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 83 publications
(233 reference statements)
0
1
0
Order By: Relevance
“…Even when employees perceive that they have good relationships with their leaders, if the leaders and employees have not reached a consensus about their roles in those relationships, employees may develop a sense of role ambiguity and withdraw their voluntary commitment to OCB (Matta et al, 2015). Indeed, a recent meta-analytic study showed that the relationship between LMX and OCB is weaker at lower levels of LMX agreement (Yuan et al, 2023), which captures the role consensus between leaders and employees (Graen & Scandura, 1987). Because we did not measure supervisorrated LMX, we could not examine this possibility in our study.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Even when employees perceive that they have good relationships with their leaders, if the leaders and employees have not reached a consensus about their roles in those relationships, employees may develop a sense of role ambiguity and withdraw their voluntary commitment to OCB (Matta et al, 2015). Indeed, a recent meta-analytic study showed that the relationship between LMX and OCB is weaker at lower levels of LMX agreement (Yuan et al, 2023), which captures the role consensus between leaders and employees (Graen & Scandura, 1987). Because we did not measure supervisorrated LMX, we could not examine this possibility in our study.…”
Section: Theoretical Implicationsmentioning
confidence: 99%